Boron Trichloride‐Mediated Synthesis of Indoles via the Aminoboration of Alkynes. Issue 21 (7th September 2018) - Lv, Jiahang; Zhao, Binlin; Liu, Li; Han, Ying; Yuan, Yu; Shi, Zhuangzhi
Abstract: We describe an efficient catalyst‐ and metal‐free aminoboration of alkynes to 3‐borylated indoles using one of the least expensive boron sources, BCl3 . The major dichloro(indolyl)borane products can be used for the in situ construction of useful 3‐Bpin indoles. This simple and mild method provides a novel and efficient approach for the synthesis of various 3‐borylated indoles with high regioselectivity and a wide substrate scope. Abstract :